2020
DOI: 10.3390/cells9112396
|View full text |Cite
|
Sign up to set email alerts
|

Vadadustat, a HIF Prolyl Hydroxylase Inhibitor, Improves Immunomodulatory Properties of Human Mesenchymal Stromal Cells

Abstract: The therapeutic potential of mesenchymal stromal cells (MSCs) is largely attributed to their immunomodulatory properties, which can be further improved by hypoxia priming. In this study, we investigated the immunomodulatory properties of MSCs preconditioned with hypoxia-mimetic Vadadustat (AKB-6548, Akebia). Gene expression analysis of immunomodulatory factors was performed by real-time polymerase chain reaction (real-time PCR) on RNA isolated from six human bone-marrow derived MSCs populations preconditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…They adhered to the plastic culture surface and formed colonies, showed expression of the surface markers CD73 (mean 99.5%), CD90 (mean 99.0%), and CD105 (mean 99.4%) and the absence of CD45, CD34, CD11b, CD19, and HLA-DR antigens in 98.3% of the cells, and demonstrated the ability to differentiate into cartilage, bone, and adipose tissue cells. Detailed results of identification analyses of the six BM-MSCs populations used in this study have been published previously in Zielniok et al (2020) ( Supplementary Tables S1–S3 , donors 1–6 in [ 11 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They adhered to the plastic culture surface and formed colonies, showed expression of the surface markers CD73 (mean 99.5%), CD90 (mean 99.0%), and CD105 (mean 99.4%) and the absence of CD45, CD34, CD11b, CD19, and HLA-DR antigens in 98.3% of the cells, and demonstrated the ability to differentiate into cartilage, bone, and adipose tissue cells. Detailed results of identification analyses of the six BM-MSCs populations used in this study have been published previously in Zielniok et al (2020) ( Supplementary Tables S1–S3 , donors 1–6 in [ 11 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies to date have demonstrated the extensive role that hypoxia and its associated transcriptional changes play in maintaining the therapeutic properties of MSCs [ 7 , 23 , 24 , 25 , 26 ]. And the fact that the transcription factor HIF-1α is a principal mediator of these changes is supported by positive results from studies involving its pharmacological stabilization [ 11 , 27 , 28 , 29 ]. However, in the present study, we showed that hypoxic preconditioning and pharmacological stabilization of HIF-1α by Vadadustat are markedly distinct in their effect at the gene expression level in MSCs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations